The influence of changes in sprint ability on the sled velocity profile during the skeleton start - Colyer, S. L.; Stokes, K. A.; Bilzon, J. L. J.; Salo, A. I. T. (ISBS - Conference Proceedings Archive (Konstanz), 2016)
Sprint times are key predictors of skeleton start petformance, but the effect of enhancing sprint ability on the development of sled velocity is unknown. Twelve well-trained skeleton athletes performed three dry-land push-starts and three 30-m sprints before and after 16 training weeks. Sled velocity profiles were characterised using three descriptors (pre-load velocity, pre-load distance and load effectiveness) and a sled acceleration index was used to evaluate performance. Increases in pre-load velocity and distance were related to improved sprint times. However, enhanced sprint ability did not guarantee a faster start as reductions in load effectiveness were also observed when higher velocities were attained. Coaches could supplement physical conditioning with load technique training to potentially improve the transfer of training-induced sled velocity increases across the loading phase.